(untitled) (Interdisciplinary Studies Journal, 2025)
Language communicates feelings, knowledge, and ideas, and is permeated by the experience of the one who produces it; therefore, it is associated with individual cognition. Thus, meaning is generated through the interaction between the body and the environment, as proposed by Cognitive Semantics. From this perspective, the present research develops its objective: the analysis of experience reports found in the e-book Policies for Teacher Training Initiation at IEL/UFCAT: knowledge, practices, and experiences in the Pedagogical Residency Program (2022). Based on the principles of image schemas and basic-level categories, excerpts from the corpus were analyzed, extracted, and categorized in Tables 1, 2, and 3. This is a qualitative study, as it is interpretive, descriptive, and analytical. To select the reports, the academic background of the authors/residents was considered. Finally, by highlighting the residents’ production, we could verify—through the excerpts—the importance of the program and which experiences within it allow students, and us, to conclude its relevance in the teacher training process.